Study of thorium retention using different functionalized resins (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Thorium (Th⁴⁺), a naturally occurring radioactive element often co-existing with rare earth elements (REEs), poses significant environmental, radiological, and regulatory concerns during REE extraction but also presents potential recovery opportunities as a valuable by-product. Effective thorium removal and retention are therefore essential for sustainable REE purification processes and for ensuring safe radioactive waste management. This study investigates the thorium adsorption behaviour and kinetic characteristics of three functionally distinct ion exchange resins which is WA21j (a weak base anion exchange resin), PE-F (a fluoride-based chelating resin), and PM401 (an iminodiacetate-functionalized chelating resin). Batch adsorption experiments were conducted using a 10 ppm Th⁴⁺ solution and 0.5 M ammonium sulphate under controlled agitation and temperature conditions by using the agitation shaker to evaluate performance consistency. Thorium concentrations were quantified by inductively coupled plasma–optical emission spectroscopy (ICP-OES), while adsorption data were analysed using non-linear pseudo-first-order and pseudo-second-order kinetic models to determine the rate-controlling mechanisms. Among the tested resins, PE-F exhibited the highest thorium uptake and the strongest correlation with the pseudo-second-order model (R² = 0.9921), confirming chemisorption as the dominant mechanism. PM401 showed comparable performance (R² = 0.9896), attributed to multidentate chelation via iminodiacetate groups, whereas WA21j demonstrated weaker retention due to limited amine interaction. The results emphasize the critical role of functional group chemistry in determining adsorption efficiency and selectivity. These findings highlight the potential of fluoride- and iminodiacetate-based resins for thorium recovery, radioactive waste remediation, and REE purification, providing valuable guidance for future development of efficient and sustainable ion exchange systems.
Keywords: Thorium adsorption; ion exchange resin; kinetic modelling